What do landowners need to know about the carbon market facing the opportunity of a new carbon income? - Ziwen Yu (EDIS)
This publication discusses information about the structure of the carbon market in the United States and some restrictions on participation. It also provides an overview of the benefits and barriers of farmers’ or landowners’ participation in the carbon market, especially for Florida. Written by Ziwen Yu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, February 2024.